1996
DOI: 10.1093/nar/24.14.2799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Single-Strand-Specific BPV-1 Origin Binding Protein, SPSF I, as the Hela Pur  Factor

Abstract: SPSF I and II are two cellular proteins which bind specifically to single-stranded DNA. SPSF I and II binding sites are found in the minimal origin of replication of BPV-1 DNA and near the P2 promoter of the cellular c-myc gene. DNA-binding properties of the two proteins to single-stranded oligonucleotides of different lengths and sequences were quantified by determination of DNA-binding constants. The binding constant of SPSF proteins to the lower strand of the BPV-1 origin was determined to be 1.5 x 10(-10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…This interaction likely underlies the previously unrecognized ability of Pur␣ and Pur␤ to form heterodimeric ssDNA-binding complexes and is likely of consequence given the diverse functional roles attributed to Pur␣. For example, Pur␣ has been previously implicated in DNA replication of several viral genomes (23)(24)(25) and transcriptional activation of both viral (22,26) and mammalian promoters (27)(28)(29)(30)(31)(32). In contrast, our results suggest that mouse Pur␣ and/or Pur␤ are able to repress the activity of a nearby enhancer in the context of both natural and chimeric promoters (11,14).…”
Section: Discussioncontrasting
confidence: 53%
“…This interaction likely underlies the previously unrecognized ability of Pur␣ and Pur␤ to form heterodimeric ssDNA-binding complexes and is likely of consequence given the diverse functional roles attributed to Pur␣. For example, Pur␣ has been previously implicated in DNA replication of several viral genomes (23)(24)(25) and transcriptional activation of both viral (22,26) and mammalian promoters (27)(28)(29)(30)(31)(32). In contrast, our results suggest that mouse Pur␣ and/or Pur␤ are able to repress the activity of a nearby enhancer in the context of both natural and chimeric promoters (11,14).…”
Section: Discussioncontrasting
confidence: 53%
“…21,26,27) Pur proteins have been known as the multifunctional nuclear proteins that play regulatory roles in both transcription and replication. [3][4][5][6][7][8] Recently, we also observed that pur a was essential for BC1 RNA expression in vitro as a transcriptional activator. 12) Furthermore, the protein bound to nascent BC1 RNA to form an RNP in the transcription reaction mixture containing brain nuclear extracts, suggesting a possible role in RNA export from the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…which are implicated in the control of DNA replication and transcription, [3][4][5][6][7][8] link neural BC1 RNA to microtubules (MTs).…”
mentioning
confidence: 99%
“…This list is composed of the genes encoding myelin basic protein, TGF-␤1, smooth muscle ␣ actin, c-Myc, neuropeptide Y, the ␤ 4 subunit of the nicotinic Ach receptor, the neuron-specific protein FE65, and CD43 (18,25,(31)(32)(33)(34)(35)(36)(37)(38). The CD11c and CD43 genes are the first described to be controlled by Pur␣ which are expressed specifically in leukocytes and which produce molecules directly responsible for leukocyte adhesion during inflammation.…”
Section: Discussionmentioning
confidence: 99%